(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This exploratory study, using a qualitative approach, sought to provide an initial understanding of digital platforms and Big Tech, focusing specifically on the Brazilian context. The research was structured in three stages: analysis of the main technology companies, survey of studies on the regulation of Big Tech in Brazil, and systematization of the data found. Throughout the research, it was observed that, although Big Tech promotes connectivity and innovative solutions, it can also foster social inequalities, make jobs precarious, and influence fundamental aspects of daily life. The concentration of power in the hands of a few corporations intensifies these challenges, especially in the United States, affecting information flows, the digital economy, and innovation. Mass data collection, disinformation, and hate speech are clear risks, and a comparison of international regulatory models highlights the urgent need for a more robust regulatory framework in Brazil. The study concluded that Big Tech regulation must be collaborative and transnational